2012 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--21224
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Teaching Engineering Self-Efficacy Scale (TESS) for K-12 Teachers

Abstract: She received her Ph.D. in educational psychology with specialty in gifted education and holds a B.S. degree in astronomy and meteorology and two master's degrees in astronomy and astrophysics and research methods and measurement. Her work centers on development and validation of instruments, particularly useful for P-16 STEM education settings and investigation of P-16 students' spatial ability to understand its association with their academic performance and to identify their talents in STEM fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…The Teaching Engineering Self-Efficacy Scale (TESS), originally designed to assess the engineering teaching self-efficacy of K-12 teachers, was adapted for use [35,36]. The scale included 41 questions, spanning six subscales.…”
Section: Methodsmentioning
confidence: 99%
“…The Teaching Engineering Self-Efficacy Scale (TESS), originally designed to assess the engineering teaching self-efficacy of K-12 teachers, was adapted for use [35,36]. The scale included 41 questions, spanning six subscales.…”
Section: Methodsmentioning
confidence: 99%
“…The four scales, prepared specifically for this study, were developed using the self-efficacy scale guidelines from Bandura (2006). Despite being novel scales the constructs were influenced by concepts outlined in the literature with the style, structure and purpose of the questions used based on those from the widely used and validated TESS scales (Yoon et al, 2012), the Maths Self-Efficacy scale (MSES, adapted for a science and engineering focus) (McMullen et al, 2012), the Science teaching outcome expectancy (version B for pre-service teachers) (Enoch & Riggs, 1990) and the STEBI-B tool (comprised of two subscales that measure Bandura's psychosocial construct) (Enoch & Riggs, 1990). Bleicher (2004) confirmed the integrity of the STEBI-B tool but found that the use of the phrase 'some students' instead of 'students' appeared to affect how respondents interpreted the statements (i.e.…”
Section: Questionnaire Designmentioning
confidence: 99%
“…Analyses were performed for nine of the 11 sites, comparing the Likert-scale scores of teacher self-efficacy for teaching engineering (a personal belief in their ability to incorporate design activities into their classroom) before and after workshop participation. The instrument, Teaching Engineering Self Efficacy (TESS) developed by Yoon, Evans, & Strobel (2012) was used for this analysis. The TESS includes items such as, "I can discuss how engineering is connected to my daily life" and "I can promote a positive attitude toward engineering learning in my students."…”
Section: Findings and Analysismentioning
confidence: 99%